2014
DOI: 10.1016/j.envpol.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical associations and availability of cadmium (Cd) in a paddy field system, northwestern Thailand

Abstract: The Mae Tao watershed, northwest Thailand, has become contaminated with cadmium (Cd) as a result of zinc ore extraction (Padaeng deposit) in the nearby Thanon-Thongchai mountains. Consumption of contaminated rice has led to documented human health impacts. The aim of this study was to elucidate transfer pathways from creek and canal waters to the paddy field soils near Baan Mae Tao Mai village and to determine the relationship between Cd speciation in the soil and uptake by rice plants. Transfer mainly occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 61 publications
2
46
0
Order By: Relevance
“…All have limitations and all generate operationally defined fractions (see review by (Bacon and Davidson, 2008), but they are nonetheless useful for identifying easily extractable vs recalcitrant element contents and for comparative purposes. The scheme devised by the Community Bureau of Reference (BCR) (Ure et al, 1993) has been employed extensively to examine metal fractionation in river sediments (Martinez-Santos et al, 2015;Pulford et al, 2009), aquaculture sludges (Nemati et al, 2011), sewage sludge (Scancar et al, 2000), urban soils (Gál et al, 2008;Madrid et al, 2007), agricultural soils (Kosolsaksakul et al, 2014), upland peat soils (Bacon et al, 2006), battlefield soils (Oliver et al, 2008) and in soils were pollution remediation trials (e.g. immobilisation with biochar or by zeolite formation) have been conducted (Belviso et al, 2010;Ippolito et al, 2017), hence it was chosen for this study.…”
Section: Element Fractionation (Bcr Sequential Extraction)mentioning
confidence: 99%
“…All have limitations and all generate operationally defined fractions (see review by (Bacon and Davidson, 2008), but they are nonetheless useful for identifying easily extractable vs recalcitrant element contents and for comparative purposes. The scheme devised by the Community Bureau of Reference (BCR) (Ure et al, 1993) has been employed extensively to examine metal fractionation in river sediments (Martinez-Santos et al, 2015;Pulford et al, 2009), aquaculture sludges (Nemati et al, 2011), sewage sludge (Scancar et al, 2000), urban soils (Gál et al, 2008;Madrid et al, 2007), agricultural soils (Kosolsaksakul et al, 2014), upland peat soils (Bacon et al, 2006), battlefield soils (Oliver et al, 2008) and in soils were pollution remediation trials (e.g. immobilisation with biochar or by zeolite formation) have been conducted (Belviso et al, 2010;Ippolito et al, 2017), hence it was chosen for this study.…”
Section: Element Fractionation (Bcr Sequential Extraction)mentioning
confidence: 99%
“…The International Water Management Institute (IWMI) investigated 524 paddy soils in Thailand and found that Cd concentrations were 0.5-284 mg/kg (Simmons et al 2005). Kosolsaksakul et al (2014) stated that paddy fields were severely contaminated by zinc ore extraction in the Mae Tao watershed of northwest Thailand, and Cd contents there ranged from 2.5-87.6 mg/kg. Nevertheless, Cd background concentrations in Thai soils were only 0.002-0.14 mg/kg (Pongsakul and Attajarusit 1999).…”
Section: Anthropogenic Pollution Sources Analysismentioning
confidence: 99%
“…Rice (Oryza sativa L.) is a major cereal crop cultivated and consumed worldwide; it is the second most important cereal crop after wheat in terms of area cultivated and consumption rate [9]. Rice growth and development are eminent at all stages for ensuring seedlings development and yield formation.…”
Section: Introductionmentioning
confidence: 99%